dc/dc-omriktarplattform med DPA-switch för telekomprodukter - Salazar Askenberg, Beneharo; Håkansson, Johan (My University, 2005)
In recent years, the penetration of new players on the telecom market has drastically increased the work pace, affecting both design and production. In this report the technical and economical potential of a DC/DC converter platform is investigated, in order to shorten the time of the design process. This is done in comparison with the present discrete type designs. Power Integrations offers a product, the DPA-Switch(tm), enabling this. By developing a wide DC/DC converter platform based on the DPA-Switch(tm), many advantages are gained. The component count is decreased by up to 48 % and the yield increases by up to 2.9 % which in all yields a cost reduction by up to 43 % or EUR390 000 for 100 000 manufactured units. The time needed for the design process is shortened compared to earlier development processes as shown by the fact that two functional converters were developed and tested during less than 20 weeks. The technical advantages are also considerable. The level of integration and the robustness increases while the complexity decreases. By using synchronous rectification, an efficiency surpassing 90 % is achieved. The disadvantage when using a specialized component such as the DPA-Switch(tm) is that it only has a single source, meaning there's only one supplier. The goal is to have multiple suppliers of the same, or equivalent component, to secure availability and delivery. An evaluation of Power Integrations has also been conducted and it's concluded that the company possesses both the technical know-how and costumer support to be of interest as a potential supplier and business partner to Ericsson Microwave Systems AB.
Keywords: Elkraftteknik; Electric power engineering